AN EXPLORATION OF BARRIERS IN LEARNING TO SPEAK ENGLISH IN ONLINE SETTING AMIDST COVID-19 PANDEMIC: A CASE OF SOPHOMORE STUDENTS IN AN INDONESIAN ISLAMIC UNIVERSITY - Aisyah Sunarwan; Ahmad Madkur; Bima Dimas Ade Putra (Jurnal Visi Ilmu Pendidikan, 2022)
Abstract Despite the global recognition of online learning as the best available option to keep enacting educational practices, particularly foreign language learning,  amidst the Covid-19 pandemic, many concern about the constraints faced by students in this unpredicted distance learning. Involving second-year students in an Islamic state university in the province of Lampung, this study aimed to investigate EFL leaners’ barriers in learning speaking in online classroom and how they cope with the barriers. The data were generated through open-ended questionnaires and then analyzed using Miles and Huberman Model. The findings of the study classified three types of barriers, namely technical barriers such as bad internet connection and running out of data quota, linguistic barriers such as by lack of vocabularies, grammar and pronunciation, and personal emotional barriers such as lack of confidence and afraid of making mistakes.  Meanwhile, the coping strategies with these obstacles were using more providers and finding area with good signal for technical strategies. For linguistics Strategies, learners listened the conversation and the song, memorized more vocabularies, comprehended more grammar, Reading a lot and highlight the unknown words, found the meaning of unknown words from dictionary, Watched more videos and films, discussed everything in English with more friends, practice to speak in front of the mirror and recorded it.  While in Personal Emotional, learners increased their confidence by forcing and convincing themselves to speak and always keep trying, everything they felt was the challenge, ignored of being afraid on making mistakes, not be panic and take a deep breath to make them relax and enjoy every situation. Keywords: English speaking, barriers, online learning, Covid-19